Gênero e saúde mental na atenção primária : a mulher como foco de investigação - Saraiva, Kaelly Virgínia de Oliveira (2008)
The promotion of female health is na issue that involves questions concerning gender inequalities and the autonomy of the woman with regards to her own body. The relationship between diseases and social factors that influence the process of health and sickness in women are aspects that demand analysis, considering women as clients that need an integral approach that join the mental health with the ginecological and obstetric aspects. In the promotion of health of the human subject as a holistic being, it also becomes necessary to engage more diverse issues, including mental health and primary care. Faced with this vision, our goal in this research is to analyze the way women understand and deal with mental suffering within the perspective of gender and integral care; and to identify the demands of the woman with some type of mental suffering related to the promotion of her health. In order to do that, the decisions and methodological tools were: qualitative, exploratory research, involving thirteen women with mental suffering, being cared for by the services of mental health or women care, in the city of Fortaleza, in the period of September 2007 to March 2008. The places chosen for the study were the Center for Psicosocial Care (CAPS) of the Walter Cantídio University Hospital, and the Center for Family Development (CEDEFAM), both belonging to the Federal University of Ceará (UFC). The different collection tools included: direct observation, semi-structured question form applied through direct interview, field diary and genogram of the women’s families. The analysis of the information was made by means of cathegories. With the characterization of the women researched, the following profile was obtained: ages between 22 and 47 years old; most are mixed race, unemployed, without personal income, surviving with an average family income of R$450,00; low level of literacy. Most maintain a relationship of the consensual union typ. The parity of the women researched is high, with most having had their firs pregnancy as teenagers. With regards to situations of violence, several have already suffered or are suffering domestic violence, characterized as interpersonal and intrafamiliar, including physical and mental violence. Most suffer of depression, three have bipolar disturb and two are schizophrenic. The most frequent Nursing diagnostics were: anxiety, low self esteem, disturbances in the energy field, verbal communication impaired, inefficient family control of the therapeutic regimen, lack of hope, risk of human dignity compromised, spiritual angst, stress overload, dysfunctional family processes, home maintenance impaired, inefficient patterns of sexuality, risk of loneliness, risk of suicide, chronic sadness. In the epidemiologic survey carried out in the women health service (CEDEFAM), of 295 pregnant women that received prenatal care from 2004 to 2008, 23% showed symptoms or complaints of psychological suffering, revealed in the Nursing diagnostics. In view of these results, we can conclude that the current medicalization of the mental health and women health services (gynecologic – obstetric) promotes a dicotomic and fragmented care, incapable of dealing with the holistic and integral needs of the female being. Thus, there is no interchangeability between the two services which, being of distinct natures, work in isolation. In the existence of the woman with mental disturb, the issues of gender are not dealt with, as well as in the care practices of the services that are specific to the women’s health, the need of the promotion of mental health are not considered. It becomes necessary for the professionals to treat the women that experience mental disease or any psychological suffering condition as a complete human being, with all her peculiarities, including the sexual-reproductive ones. This humane and therapeutic attitude, that is found beyond the realms of medicalization, runs through the merely biological and biophysical promotion of health, reaching a transcendental sphere directed towards the human nature as regards to the gender and the female being, in face of which the quality of life is also promoted, even in a world that, despite containing conflicting relationships, can become a space for intimate, personal self- realization, of the practice of altruism and of the equality of beings and, why not, of the enjoinment of being what one is: woman.